'Centres of excellence' for artisanal and small-scale gold mining in Tanzania: Assumptions around artisanal entrepreneurship and formalization. Issue 2 (April 2020) - Kinyondo, Abel; Huggins, Christopher
Highlights: Training and demonstration centres are part of strategies to formalize ASM. In sub-Saharan Africa, such centres have a mixed record of success. In 2019 Tanzania established four training, processing and demonstration centres. The Tanzanian centres are partly based on assumptions that ASM is entrepreneurial. Success of the centres in facilitating formalization will depend on affordability and flexibility. The centres may not succeed if they are linked to coercive forms of formalization. Abstract: The Africa Mining Vision reiterates the importance of training centres or 'centres of excellence' (COEs) for artisanal and small-scale mining but historically, these have had mixed results, partly due to a lack of understanding of demand for services. Recently, understanding of artisanal and small-scale mining (ASM) organizational and financial structures has improved, allowing for a more nuanced comparison of formalization policies that emphasize the 'entrepreneurial' nature of ASM operators and those that foreground the importance of poverty as a driving factor. With World Bank support, Tanzania has recently established several COEs including two for the artisanal and small-scale gold mining sector. This article examines the potentials of these centres, based on key informant interviews, as well as a literature review of experiences from other African countries. Further, we analyse activities planned at COEs, within the Tanzanian institutional and policy context, which tends to treat ASM as 'entrepreneurs'. We explore implications of the Tanzanian approach for potential formalization of ASM and transformation of ASM operators into medium-scale mining firms; and identify some institutional tensions and risks involved in implementing the COE approach.